Peningkatan Kemampuan Sistem Manajemen Informasi Aparatur Desa Berbasis IT Dalam Upaya Meningkatkan Kesejahteraan Masyarakat Pesisir - Sani, Asrul (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2019)
Information and Communication Technology (ICT) has reached rural areas. This community service program (KKN PPM) aims to increase the knowledge of village officials and ability to use ICT in managing their local government. Students majored in informatics, mathematics and statistics were involved in the program located in three coastal areas of Kapoiala sub-district, Konawe district. The method used was observation, training and mentoring. It was found that prior to KKN PPM the knowledge level of village officials relating to ICT was still very low. It was due to some factors such as the low level of education, daily activities not requiring ICT and lack of digital mindset. The training and mentoring provided showed an increase in understanding of ICT for the village officials, the community as well as the youth and students. SIMADESTERA and Website for each village were successfully established. However, the skills of the officials in using ICTs have not improved significantly. The obstacle was their low motivation to complete the training due to their jobs for daily lives. In addition, it was still lack of ICT infrastructure in supporting the maintenance of SIMADESTERA and Webdesa. The youth and students showed sufficiently high motivation and they are skilled enough in using ICT. These groups are potential to assist village governments, especially in operating SIMADESTERA and Webdesa.